Determinants of ATM Adoption in Kenya: An Empirical Study of Bankers’ Attitudes - Nyangosi, Richard; Arora, J.S (Gyan Management Journal, 2009)
Tlie new electronic age has transformed the marketing of hanking services. Customers nowadays demand new and differentiated financial products and services. In the essence, banks must search for new strategies of marketing their products and services. With pressure from dynamic and advancement o f inforrnation technology, different electronic distribution channels have bee adopted to meet the demands of customers. The objective of this paper is to examine the adoption of e-banking channels by Kenya banks, the services provided through ATM channel in Kenyan banks, and also factors influencing banks to adopt ATM banking. The data for the study was obtained from primary source with the use of well structured and pre-tested questionnaires, which were distributed among top and middle level bank executives in Kenyan hanks. The findings revealed that am.ong thee-channels surveyed, ATM was fthe most adopted technology by the banks under survey. Further, it was revealed tli.at non-complexity o ATM technology and convenience nature of ATM to many customers, were the major factors encouraging the bankers in advancing to e-banking arena